Watson Kirkconnell on "The place of Slavic studies in Canada": a 1957 speech to the Canadian Association of Slavists. Issue 4 (21st October 2016) - Coleman, Heather J.
ABSTRACT: This article introduces and reprints a speech by Watson Kirkconnell to the Canadian Association of Slavists in 1957. Watson Kirkconnell (1895—1977) was an influential Canadian scholar, university administrator, Baptist activist, and prodigious translator of verse. The introduction discusses his significant role in the development of Slavic and East European studies in Canada, as founder of the Humanities Research Council of Canada, and as an early promoter of multiculturalism in Canada. In his speech, Kirkconnell discussed his personal encounter with Slavic studies and the early development of the field in Canada, his role in the pre-history of the Canadian Association of Slavists, and the importance he accorded to fostering critical knowledge of the Slavic and East European societies and cultures in Canada. Slavic studies, he argued, were necessary both intellectually and politically: the Slavic and East European literatures constituted "major stones in the arch of modern civilization"; moreover, in the atmosphere of the Cold War, knowledge of the languages and societies of Soviet-dominated Central and Eastern Europe would play a fundamental role in the fight against communism.